Handbook of plant-based fermented food and beverage technology - Hui, Y. H. (Yiu H.); Evranuz, E. Özgül.; Arroyo-López, Francisco Noé. (Boca Raton, Fla. : CRC Press, 2012)
"This second edition of a bestseller examines a wide range of starter cultures and manufacturing procedures for popular plant-based food products. The text focuses on the quality of the final food product, flavor formation and new advances in starter cultures for dairy fermentations using recent examples that depict the main species used, their characteristics, and their impact on the development of other fermented foods. Also new to the second edition: sections on fermented fruit such as apple cider, fermented specialties such as vanilla, and U.S. permitted food ingredients derived each fermented product. Covers numerous fermentation procedures by reviewing the type of raw material used, its pretreatment, the temperature/climate, and the conditions of the fermentation process. Discusses various types of starter cultures and their preparation prior to use. Outlines some of the flaws that may be found in sour cream products, their causes, and possible ways to prevent these defects. Analyzes the sensory characteristics of various fermented food products including texture, color, and aroma"--
pt. 1. Introduction -- pt. 2. Soy products -- pt. 3. Fruits and fruit products -- pt. 4. Vegetables and vegetable products -- pt. 5. Cereals and cereal prodcuts -- pt. 6. Specialty products -- pt. 7. Fermentation and food ingredients.
Rev. ed. of: Handbook of food and beverage fermentation technology / edited by Y.H. Hui ... [et al.]. 2004.
"Handbook of food and beverage fermentation technology" is the first edition of "Handbook of plant-based fermented food and beverage technology" and "Handbook of animal-based fermented food and beverage technology."
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Fermented foods -- Handbooks, manuals, etc; Beverages -- Microbiology -- Handbooks, manuals, etc; Fermentation -- Handbooks, manuals, etc; Plant proteins as food -- Handbooks, manuals, etc; Plant products -- Handbooks, manuals, etc; Electronic books